2015
DOI: 10.1097/bcr.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prediction of Prolonged Pruritus After Severe Burns

Abstract: Years after injury, pruritus is a common and severe problem for many burn patients. However, its characteristics and consequences are often only partially described. The authors therefore performed a prospective detailed examination of burn- and individual-related factors and considered those in relation to pruritus severity. Sixty-seven consecutive burn patients were assessed during acute care, and at 3 and 12 months postburn regarding preburn psychiatric disorders, health-related quality of life, post trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…They revealed that more than two thirds of patients suffer from paresthesia, which the most frequent are tingling, stiffness, numbness or pinpricks (146,147). Itching is also a common post-burn paresthesia and affects at least 70% of burned patients at 1 or 2 years post-burn, and still around 40% in the following decade (12,148,149). The itching prevalence also depends on the injured anatomic sites.…”
Section: Itching and Paresthesiamentioning
confidence: 99%
“…They revealed that more than two thirds of patients suffer from paresthesia, which the most frequent are tingling, stiffness, numbness or pinpricks (146,147). Itching is also a common post-burn paresthesia and affects at least 70% of burned patients at 1 or 2 years post-burn, and still around 40% in the following decade (12,148,149). The itching prevalence also depends on the injured anatomic sites.…”
Section: Itching and Paresthesiamentioning
confidence: 99%
“…They are included in this section for the purpose of clinical classification. Approximately 86% of patients with keloids have itch, which commonly affects the borders of keloid, and pruritus affects 76% of patients with burn lesions [62,63] . EPPER is a rare entity, which may present in the scalp when radiation has been used in this area.…”
Section: Other Skin Lesionsmentioning
confidence: 99%
“…While differences in duration of scratching between sham‐treated and burn wound animals were highly significant, the average duration of scratching in burn wound animals (e.g., 46 second/hour in Week 6–12) is, in an absolute sense, not very impressive. Thus, the intensity of postburn itch in rats seems less debilitating than that described in humans . Nevertheless, this is the first time that increased scratching behavior is found in a burn wound animal model.…”
Section: Discussionmentioning
confidence: 63%
“…4 Complaints commonly start within one month postburn, with a peak at six months. 5 The prevalence of itch following burns is high: 6,7 up to 87% of the adults report mild to severe itching at three months postburn. 6 In 44% of the patients itch sensation was still present seven years postburn.…”
mentioning
confidence: 99%